2013
DOI: 10.1093/nar/gkt999
|View full text |Cite
|
Sign up to set email alerts
|

Stress-induced changes in gene interactions in human cells

Abstract: Cells respond to variable environments by changing gene expression and gene interactions. To study how human cells response to stress, we analyzed the expression of >5000 genes in cultured B cells from nearly 100 normal individuals following endoplasmic reticulum stress and exposure to ionizing radiation. We identified thousands of genes that are induced or repressed. Then, we constructed coexpression networks and inferred interactions among genes. We used coexpression and machine learning analyses to study ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 54 publications
2
15
0
Order By: Relevance
“…However, more recent studies have identified common responses to different stresses within a given cell type, albeit with smaller magnitude transcript changes than seen in yeast. Nayak et al (2014) leveraged statistical power in a large study of B cell responses to ER stress and ionizing radiation, finding substantial overlap in response to the two stresses. Several studies interrogating p53 activity (see below) identified a common response that persists across several cell lines and conditions: induced genes are related to stress defense and regulation of cell cycle or apoptosis and repressed genes are linked to rDNA transcription, ribosome biogenesis, translation and cell cycle/apoptotic factors that work antagonistically to induced genes (Cairns and White 1998; Budde and Grummt 1999; Zhai and Comai 2000; Wei et al 2006; Menendez et al 2009; Nikulenkov et al 2012; Schlereth et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, more recent studies have identified common responses to different stresses within a given cell type, albeit with smaller magnitude transcript changes than seen in yeast. Nayak et al (2014) leveraged statistical power in a large study of B cell responses to ER stress and ionizing radiation, finding substantial overlap in response to the two stresses. Several studies interrogating p53 activity (see below) identified a common response that persists across several cell lines and conditions: induced genes are related to stress defense and regulation of cell cycle or apoptosis and repressed genes are linked to rDNA transcription, ribosome biogenesis, translation and cell cycle/apoptotic factors that work antagonistically to induced genes (Cairns and White 1998; Budde and Grummt 1999; Zhai and Comai 2000; Wei et al 2006; Menendez et al 2009; Nikulenkov et al 2012; Schlereth et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…While the ER stress response pathway is well studied, it is only recently that we are beginning to understand how genetic variation impacts an individual’s response to ER stress. ER stress-responsive gene expression is variable among immortalized human B cells and this variation is likely heritable [ 7 , 8 ]. We have recently shown that ER stress responsive gene expression is also highly variable across wild-derived, inbred Drosophila melanogaster strains, and that susceptibility to ER stress in these strains is associated with SNPs in canonical ER stress genes, such as Xbp1 , as well as many novel candidate ER stress genes [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studying variation in ER stress response also provides the opportunity to nominate and eventually functionally validate new genes that influence the ER stress response, genes that may be missed by studying only one inbred laboratory strain [ 9 ]. Studies of human ER stress variation are limited to immortalized cell lines [ 7 , 8 ] and cannot be extended to in vivo studies. The mouse, however, is uniquely suited for understanding the genetic variation in ER stress response, both in cultured cell lines as well as in vivo , and allows for direct extension to and testing in models of human disease.…”
Section: Introductionmentioning
confidence: 99%
“…Upon arrival at the Golgi ATF6 undergoes regulated intramembrane proteolysis, releasing a transcriptionally active N‐terminal portion of 50 kDa which enters the nucleus and promotes transcription of UPR genes, including XBP‐1 and BiP (Figure ) . The UPR up‐regulated genes includes ORP150 and SIL1 , which increase at both transcriptional and protein levels .…”
Section: Sensing Er Stress: the Role Of Bip In The Uprmentioning
confidence: 99%